(untitled) (Research, Society and Development, 2021)
Protected areas are an important instrument for the conservation of environmental systems. In view of the need to disseminate protected areas as a means of nature conservation and consequent maintenance of human life, the article in question sought to contribute to the deepening of this theme, with a view to improving the current framework in environmental protection. Thus, the article aims to present a bibliographic review of the main works published on the theme of protected areas both in an international and a national context. It is noticeable that from the 60’s and 70’s onwards the number of areas created per year started to increase. Some explanations are possible for this increase, one of them being the influence of the great Conferences of the United Nations held during this period. Through the references brought in the work, it is observed that even though an increase in the creation of areas has been identified, environmental protection still lacks the attention of governments in many nations.